Pengembangan Modul Elektronik Menulis Teks Tanggapan Berbasis LMS Moodle dengan Muatan Ekoliterasi untuk Kelas 9 - Sella Auliya Rahmah; Didin Widyartono (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
This research purposed to produce a Moodle module based ecoliteracy for 9th grade. This study used five methods, (1) preliminary analysis, (2) product development, (3) expert validation and revision, (4) small-scale field trials and revision, and (5) large scale product trial. This research produces a Moodle module with ecoliteracy in its content and presentation which has been validated by material, media, and language expert with certain qualifications. This study result is suitable product that get validation score 87.5% for material, 92.5% for media, and 70.5% for language. The result from small field trials is 75%, and 87.5% for large field trials, the product declared as suitable to use. This study ecoliteracy in the module content is contained in its themes, learning objectivities, materials, exercise, and cases that students must responses. Ecoliteracy in the module presentation is include in text, images, audios, and videos.